(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The value of the human capital of the countries of the world was calculated by the staff of the World Bank. By taking into account the funds spent by the state, family, companies, businessmen and various funds for the formation of human capital, the size of the expenses directed to the formation and improvement of the human capital of the society is determined every year.